2018
DOI: 10.1177/0310057x1804600509
|View full text |Cite
|
Sign up to set email alerts
|

Inhalational versus Propofol-Based Total Intravenous Anaesthesia: Practice Patterns and Perspectives among Australasian Anaesthetists

Abstract: Increasing evidence suggests that total intravenous anaesthesia (TIVA) may be the preferred anaesthetic for cancer resection surgery. To assist the preparation of a randomised controlled trial (RCT) examining Volatile (versus TIVA) Anaesthesia and Perioperative Outcomes Related to Cancer (VAPOR-C) we developed an 18-question electronic survey to investigate practice patterns and perspectives (emphasising indications, barriers, and impact on cancer outcomes) of TIVA versus inhalational general anaesthesia in Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 24 publications
(29 reference statements)
4
25
0
Order By: Relevance
“…Regrettably, surveys take time to fill in, and we feel that one questionnaire and one follow up e-mail to a thousand anaesthetists keeps the balance between an acceptable sample size and not harassing our already busy colleagues. Our response rate is similar to recently published surveys from the ANZCA clinical trials network [3234] and we believe that our results are likely to be representative and are worth reporting. As survey research is vulnerable in that it may deliver socially desirable answers, we have attempted to minimize this by maintaining respondent anonymity [35].…”
Section: Discussionsupporting
confidence: 87%
“…Regrettably, surveys take time to fill in, and we feel that one questionnaire and one follow up e-mail to a thousand anaesthetists keeps the balance between an acceptable sample size and not harassing our already busy colleagues. Our response rate is similar to recently published surveys from the ANZCA clinical trials network [3234] and we believe that our results are likely to be representative and are worth reporting. As survey research is vulnerable in that it may deliver socially desirable answers, we have attempted to minimize this by maintaining respondent anonymity [35].…”
Section: Discussionsupporting
confidence: 87%
“…51 Surveys of current clinical practice report that anesthesiologists generally have a preference for volatile anesthesia. 52,53 In a survey of Australasian anesthesiologists, Lim et al reported that [ 80% of Limitations of this study include the retrospective nature of the majority of the studies. The studies also had different follow-up intervals and significant variability of baseline patient demographics.…”
Section: Discussionmentioning
confidence: 97%
“…Although it did not include the most recent reports, a meta-analysis of 21,000 patients showed that both recurrence-free survival and overall survival rates were higher in the TIVA group than in the volatile anesthesia group [29]. Despite these data, one survey revealed that most anesthesiologists preferred inhalation anesthesia [30]. As many as 43% of respondents presumed that TIVA could reduce cancer recurrence; however, only 29% of them used TIVA for cancer surgery.…”
Section: Discussionmentioning
confidence: 99%